The association of meniscal status, lower extremity alignment, and body mass index with chondrosis at the time of revision Anterior Cruciate Ligament reconstruction - Brophy, Robert H. (Am J Sports Med, 2015)
BACKGROUND: Knees undergoing revision ACL reconstruction (rACLR) have a high prevalence of articular cartilage lesions. HYPOTHESIS: The purpose of this study was to test the hypothesis that the prevalence of chondrosis at the time of rACLR is associated with meniscus status and lower extremity alignment. STUDY DESIGN: Cross sectional study. METHODS: Data from the prospective Multicenter ACL Revision Study (MARS) cohort was reviewed to identify patients with pre-operative lower extremity alignment films. Lower extremity alignment was defined by the weight bearing line (WBL) as a percentage of the tibial plateau width, while the chondral and meniscal status of each weight bearing compartment was recorded at the time of surgery. Multivariable proportional odds models were constructed and adjusted for relevant factors in order to examine which risk factors were independently associated with the degree of medial and lateral compartment chondrosis. RESULTS: The cohort included 246 patients with lower extremity alignment films at the time of rACLR. Average (SD) patient age was 26.9 (9.5) years with a BMI of 26.4 (4.6). The medial compartment had more chondrosis (Grade 2/3: 42%, Grade 4: 6.5%) than the lateral compartment (Grade 2/3: 26%, Grade 4: 6.5%). Disruption of the meniscus was noted in 35% of patients on the medial side and 16% in the lateral side. The average (SD) WBL was measured to be 0.43 (0.13). Medial compartment chondrosis was associated with BMI (p=0.025), alignment (p=0.002), and medial meniscus status (p=0.001). None of the knees with the WBL lateral to 0.625 had Grade 4 chondrosis in the medial compartment. Lateral compartment chondrosis was significantly associated with age (p=0.013) and lateral meniscus status (p<0.001). Subjects with ‘intact’ menisci were found to decrease their odds of having chondrosis by 64–84%. CONCLUSIONS: The status of articular cartilage in the tibiofemoral compartments at the time of rACLR is related to meniscal status. Lower extremity alignment and BMI are associated with medial compartment chondrosis. CLINICAL RELEVANCE: Providers and patients should be aware of the association of meniscal integrity, alignment and BMI with chondrosis at the time of rACLR. Further research into the potential benefits of interventions to optimize these parameters is warranted.